2019
DOI: 10.1123/pes.2018-0141
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting Aerobic Fitness in Youth: The Fallacy of Ratio Scaling

Abstract: In this paper, we draw on cross-sectional, treadmill-determined, peak oxygen uptake data, collected in our laboratory over a 20-year period, to examine whether traditional per body mass (ratio) scaling appropriately controls for body size differences in youth. From an examination of the work of pioneering scientists and the earliest studies of peak oxygen uptake, we show how ratio scaling appears to have no sound scientific or statistical rationale. Using simple methods based on correlation and regression, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
88
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 61 publications
(90 citation statements)
references
References 33 publications
2
88
0
Order By: Relevance
“…Ratio scaling is "convenient and traditional" (13), but it does not have a rigorous scientific rationale, is often not statistically justified, favors lighter individuals, and penalizes heavier (overweight or more mature) youth (45,46,50). Allometric scaling has challenged the "convenient and traditional" interpretation of youth aerobic fitness and indicated that, with body mass appropriately controlled for, there is a progressive increase in peakVO 2 with age in both sexes (48).…”
mentioning
confidence: 99%
“…Ratio scaling is "convenient and traditional" (13), but it does not have a rigorous scientific rationale, is often not statistically justified, favors lighter individuals, and penalizes heavier (overweight or more mature) youth (45,46,50). Allometric scaling has challenged the "convenient and traditional" interpretation of youth aerobic fitness and indicated that, with body mass appropriately controlled for, there is a progressive increase in peakVO 2 with age in both sexes (48).…”
mentioning
confidence: 99%
“…CRF, estimated by 20-meter shuttle run test (Huang et al, 2015;Westfall et al, 2018) and peak oxygen uptake (VȮ 2peak ) scaled, that is, divided, by body mass (BM) have been positively associated with cognition in some Chaddock, Hillman, Buck, & Cohen, 2011;Chaddock, Hillman, et al, 2012;Davis et al, 2011;Voss et al, 2011), but not all studies (Chaddock, Erickson, Prakash, Kim, et al, 2010;Ruiz et al, 2010) in children and adolescents. However, scaling the measures of CRF by BM has no clear physiological rationale because it may not remove the effect of body size and composition on CRF (Tanner, 1949;Welsman & Armstrong, 2019). VȮ 2peak scaled by lean mass (LM) has been considered the most appropriate method to express CRF (Loftin, Sothern, Takashi, & Bonis, 2016).…”
mentioning
confidence: 99%
“…The 20mSRT has been proposed as a suitable and feasible health indicator for international surveillance in children and adolescents (90) and as a means of evaluating physical activity interventions (89). Others have argued that estimating/ predicting peakVO 2 from 20mSRT performance scores is untenable (10), the use of per-body mass ratio scaling is fallacious (10,168), the establishment of thresholds for cardiometabolic risk in children using current criteria is indefensible (9,10), and the use of field test performance estimates of peakVO 2 to evaluate physical activity interventions is specious (12). In this lively debate, Mintjens and colleagues' (107) thoughtful systematic review of longitudinal studies of the influence of CRF in childhood and adolescence on future cardiovascular risk factors is timely.…”
Section: Commentarymentioning
confidence: 99%
“…Unfortunately, the majority of papers that directly determined peakVO 2 only reported it in ratio with body mass. It has been demonstrated theoretically (169,170) and empirically (9,168) that ratio scaling has neither a sound scientific rationale nor statistical justification. Moreover it is age-and maturity-status-driven fat free mass, not body mass, which is the most powerful morphological influence on peakVO 2 (9).…”
Section: Commentarymentioning
confidence: 99%